2017
DOI: 10.1016/j.enzmictec.2017.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic synthesis of chlorogenic acid glucoside using dextransucrase and its physical and functional properties

Abstract: Chlorogenic acid, a major polyphenol in edible plants, possesses strong antioxidant activity, anti-lipid peroxidation and anticancer effects. It used for industrial applications; however, this is limited by its instability to heat or light. In this study, we for the first time synthesized chlorogenic acid glucoside (CHG) via transglycosylation using dextransucrase from Leuconostoc mesenteroides and sucrose. CHG was purified and its structure determined by nuclear magnetic resonance and matrix-associated laser … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Lactiplantibacillus plantarum fermentation significantly enhanced the ability to scavenge free radical's DPPH when the fermenting conditions were optimized by the method of responsive surface design in fermenting sheep bone Produce antioxidant substances (active phenol metabolites, chlorogenic acid glucoside, sulforaphane) have a variety of beneficial effects on the human body Lactiplantibacillus plantarum (Ge et al, 2019;Mu et al, 2019;Ryu et al, 2019), Lacticaseibacillus rhamnosus, Lactobacillus acidophilus (Kêska and Stadnik, 2018), Leuconostoc mesenteroides (Nam et al, 2017) Metabolize phenolic acid by decarboxylase and reductase…”
Section: Exploration Of a New Way Of Glucan Biosynthesismentioning
confidence: 99%
“…Lactiplantibacillus plantarum fermentation significantly enhanced the ability to scavenge free radical's DPPH when the fermenting conditions were optimized by the method of responsive surface design in fermenting sheep bone Produce antioxidant substances (active phenol metabolites, chlorogenic acid glucoside, sulforaphane) have a variety of beneficial effects on the human body Lactiplantibacillus plantarum (Ge et al, 2019;Mu et al, 2019;Ryu et al, 2019), Lacticaseibacillus rhamnosus, Lactobacillus acidophilus (Kêska and Stadnik, 2018), Leuconostoc mesenteroides (Nam et al, 2017) Metabolize phenolic acid by decarboxylase and reductase…”
Section: Exploration Of a New Way Of Glucan Biosynthesismentioning
confidence: 99%
“…Medicinal chrysanthemum contains many flavonoids and polyphenols, with chlorogenic acid being one of the main polyphenols, and it has strong antioxidant activity, inhibits lipid peroxidation, and has anticancer effects [5] . In modern times, chrysanthemums are also used as a functional food.…”
Section: Introduction mentioning
confidence: 99%
“…Although this effect was already observed at the in vitro level, in vivo studies only confirmed it (Tajik et al, 2017). This is due to the fact that CGA is an electrophilic trapping factor and its ability to inhibit lipid peroxidation, which is triggered by free radicals (Nam et al, 2017). It has also been F I G U R E 5 Effects of chlorogenic acid and a static magnetic field on the antioxidative defense parameters -SOD (5A), GPx (5B) and CAT (5C) activity in the melanoma cells.…”
Section: Discussionmentioning
confidence: 94%
“…Although this effect was already observed at the in vitro level, in vivo studies only confirmed it (Tajik et al., 2017). This is due to the fact that CGA is an electrophilic trapping factor and its ability to inhibit lipid peroxidation, which is triggered by free radicals (Nam et al., 2017). It has also been proven that that CGA is active against the mutagenesis and carcinogenesis that is induced by various chemical carcinogens, for example, polycyclic aromatic hydrocarbons (Szaefer et al., 2004).…”
Section: Discussionmentioning
confidence: 99%